Anthropometric measures and prevalence trends in adolescents with coeliac disease: a population based study. Issue 2 (26th September 2016) - Assa, Amit; Frenkel-Nir, Yael; Leibovici-Weissman, Ya'ara; Tzur, Dorit; Afek, Arnon; Katz, Lior H; Levi, Zohar; Shamir, Raanan
Abstract : Objectives: To investigate the impact of coeliac disease (CD) diagnosis on anthropometric measures at late adolescence and to assess trends in the prevalence of diagnosed CD over time. Design: A population based study. Patients: Prior to enlistment, at the age of 17 years, most of the Israeli Jewish population undergoes a general health examination. Subjects' medical diagnoses are entered into a structured database. Interventions: The enlistment database was thoroughly searched for CD cases between the years 1988 and 2015. Medical records of 2 001 353 subjects were reviewed. Main outcome measures: Anthropometric measures at the age of 17 years. Results: Overall, 10 566 CD cases (0.53%) were identified and analysed. Median age at data ascertainment was 17.1 years (IQR, 16.9–17.4). Multivariable analysis demonstrated that boys with CD were leaner (Body Mass Index 21.2±3.7 vs 21.7±3.8, p=0.02) while girls with CD were shorter (161.5±6 cm vs 162.1±6 cm, p=0.017) than the general population. The prevalence of diagnosed CD increased from 0.5% to 1.1% in the last 20 years with a female predominance (0.64% vs 0.46%). CD prevalence was significantly lower in subjects of lower socioeconomic status and those of African, Asian and former Soviet Union origin. Conclusions: Adolescent boys with CD were leaner and girls with CD were shorter compared with the general population. However, the clinical relevance of the small differences suggests that when CD is diagnosed during childhood, final weight and height are not severely impaired. Our cohort reinforces the observed increase in diagnosed CD.